The Routledge history of American sexuality
1 online resource.
Keywords: "The Routledge History of American Sexuality brings together contributions from leading scholars in history and related fields to provide a far-reaching but concrete history of sexuality in the United States. This interdisciplinary group of authors explore a wide variety of case studies and concepts to provide an innovative approach to the history of sexual practices and identities over several centuries. Each essay interrogates a provocative word or concept to reflect on the complex ideas, debates and differences of historical and cultural opinions surrounding it. Its authors challenge readers to look beyond contemporary identity-based movements in order to excavate the deeper histories of how people have sought sexual pleasure, power, and freedom in the Americas. This book is an invaluable resource for students or scholars seeking to grasp current research on the history of sexuality and is a seminal text for undergraduate and graduate courses on American history, Sexuality Studies, Women's Studies, Gender Studies, or LGBT Studies"--